Implementasi Pasal 14 Peraturan Bersama Menteri Agama dan Menteri Dalam Negeri Nomor 9 dan 8 Tahun 2006 Terhadap Persetujuan Bangunan Rumah Ibadah di Kabupaten Kuantan Singingi - Mayindah, Kezia; Deliana, Evi; Zulwisman, Zulwisman (CV. Rayyan Dwi Bharata, 2025)
The establishment of places of worship is regulated under the “Peraturan Bersama Menteri Agama dan Menteri Dalam Negeri Nomor 8 dan 9 Tahun 2006 tentang Panduan Pelaksanaan Tugas Kepala Daerah/Wakil Kepala Daerah dalam Mempertahankan Kerukunan Umat Beragama, Mendorong Forum Kerukunan Umat Beragama, dan Pendirian Rumah Ibadah”. In practice, this responsibility has been delegated to FKUB. In general, the construction of places of worship serves not only ritual worship purposes but also social activities aligned with religious understanding, thereby providing rights to adherents. This study aims to examine the extent of the implementation, impact, and government’s role in carrying out the “PBM Agama Dan Menteri Dalam Negeri Nomor 9 Dan 8 Tahun 2006” according to its rules. This research analyzes issues related to the establishment of places of worship in Kuantan Singingi Regency, focusing on inconsistencies with the Joint Regulation. Through sociological legal research, this study identifies emerging issues, including a lack of regulatory compliance, unmet technical requirements, and unclear government responsibilities. This phenomenon has led to legal uncertainty and the cancellation of construction permits by authorized authorities. The findings reveal that the implementation of the Joint Regulation has not been properly conducted. These findings highlight the need for greater regulatory compliance and clarity in government responsibilities related to the establishment of places of worship. This study contributes to understanding the dynamics of legal enforcement and governance in the development of places of worship within the context of Kuantan Singingi Regency